Good Environmental Governance dalam Perlindungan dan Pengelolaan Lahan Gambut Berkelanjutan di Pulau Bengkalis Kabupaten Bengkalis (Lembaga Pengembangan Kinerja Dosen, 2025)
Peatlands play a crucial role in maintaining ecosystem balance and mitigating climate change; however, their existence on Bengkalis Island, Bengkalis Regency, faces significant pressure due to land-use changes, forest fires, and unsustainable management practices. This study aims to analyze the application of Good Environmental Governance (GEG) principles in the sustainable protection and management of peatlands in the region. A qualitative approach was used, employing data collection techniques such as document analysis, in-depth interviews with stakeholders, and field observations. This research adopts Belbase’s theoretical framework, which includes rule of law, participation and representation, access to information, transparency and accountability, decentralization, institutions and agencies, and access to justice. The findings reveal that GEG implementation on Bengkalis Island still encounters various challenges, particularly in terms of inter-agency coordination, community involvement, and environmental law enforcement. Nevertheless, there are positive initiatives from local governments and NGOs that promote transparent, participatory, and accountable environmental governance. The study recommends strengthening institutional capacity, enhancing local community participation, and integrating science-based policies in sustainable peatland management. With consistent application of GEG principles, the long-term protection of peatland ecosystems on Bengkalis Island can be better ensured.